ATTERBERG LIMIT PADA TANAH LEMPUNG YANG DISTABILISASI DENGAN NATRIUM KARBONAT - Srie Gunarti, Anita Setyowati (Universitas Islam 45 Bekasi, 2013)
Soil properties often have inadequate to sustain a construction or building, such as compressibility, permeability, and plastisitasnya. One method of stabilization of chemical soil stabilization as an effort to increase strength, reduce the reduction, and improving physical and mechanical properties of others. In this study, conducted observations of Clay Soil Plasticity Index values are mixed with Natrium Carbonate (Na2CO3) with a composition of 1 g of Na2CO3 for 1 kg of soil clays and brooded for 24 hours at the Laboratory of Soil Mechanics Unisma Bekasi. Then tested the limits of consistency (Atterberg Limits) to obtain the value of liquid limit and plastic limit so we get the soil plasticity index. The test results concluded that the original soil physical properties soil plasticity index value of 45.07%. Land included in the type CH (Inorganic clay with high plasticity), and within the category of very soft clay and somewhat sensitive. Soil mixed with Natrium Carbonate has a plasticity index value of 27.553%. Land included in the type of inorganic silt or organic clay with moderate to high plasticity. Natrium Carbonate is successful in reducing the plasticity index value of the land, so that the physical properties of soil clays for the better. Keywords: Natrium Carbonate, Soil clays, Chemical Stabilization, Plasticity Index